Ultra-performance liquid chromatography for quantification of amphotericin B plasma concentrations after use of liposomal amphotericin B. (22nd December 2020) - Van Daele, Ruth; de Beer, Yvo; Croes, Sander; Aarnoutse, Rob; Wauters, Joost; Maertens, Johan; Spriet, Isabel; Brüggemann, Roger J
Abstract: Objectives: Liposomal amphotericin B is widely used to treat life-threatening invasive fungal infections and has replaced conventional amphotericin B deoxycholate due to its more favourable toxicity profile. Despite the fact that liposomal amphotericin B has been licensed for several decades, there is still a paucity of clinical pharmacokinetic data. An assay for the quantification of amphotericin B is necessary to allow the study of its pharmacokinetics. Methods: A UPLC-photodiode array (PDA) analytical method was developed and validated (linearity, accuracy, precision, dilution integrity, carry-over, selectivity and stability) in accordance with EMA requirements. Results: The analytical method was validated over a concentration range of 0.5–50.0 mg/L. Accuracy ranged from 97.6% to 112.1% and within-day repeatability and between-day reproducibility from 1.0% to 6.6% and from 0.4% to 4.6%, respectively, dependent on the concentration. Originally, the goal was to develop an analytical method to separate the liposomal and free amphotericin B fractions, but this was not achieved. Difficulties and bottlenecks encountered are presented. Conclusions: A UPLC-PDA analytical method was developed to quantify total amphotericin B in plasma after the use of liposomal amphotericin B.